1997
DOI: 10.1523/jneurosci.17-08-02921.1997
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Glutamatergic Neurotransmission by Ketamine: A Novel Step in the Pathway from NMDA Receptor Blockade to Dopaminergic and Cognitive Disruptions Associated with the Prefrontal Cortex

Abstract: Subanesthetic doses of ketamine, a noncompetitive NMDA receptor antagonist, impair prefrontal cortex (PFC) function in the rat and produce symptoms in humans similar to those observed in schizophrenia and dissociative states, including impaired performance of frontal lobe-sensitive tests. Several lines of evidence suggest that ketamine may impair PFC function in part by interacting with dopamine neurotransmission in this region. This study sought to determine the mechanism by which ketamine may disrupt dopamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

91
1,219
5
25

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,633 publications
(1,367 citation statements)
references
References 68 publications
91
1,219
5
25
Order By: Relevance
“…Glutamate and the NMDA-R are essential factors in the plasticity response of the basalganglia (Schmidt, 1998) and glutamatergic activity is secondary only to dopaminergic activity in these structures (Nieoullon, 2002). As NMDA antagonism enhances both glutamate and dopamine release in components of corticostriato-thalamic circuitry (Moghaddam et al, 1997), it is feasible that this enhancement is responsible for the impairment in procedural learning observed in the current study. Previous research has found that administration of a dopamine antagonist can reverse ketamine-induced impairments on the WCST, which has a procedural learning component (Krystal et al, 1999).…”
Section: Discussionmentioning
confidence: 68%
“…Glutamate and the NMDA-R are essential factors in the plasticity response of the basalganglia (Schmidt, 1998) and glutamatergic activity is secondary only to dopaminergic activity in these structures (Nieoullon, 2002). As NMDA antagonism enhances both glutamate and dopamine release in components of corticostriato-thalamic circuitry (Moghaddam et al, 1997), it is feasible that this enhancement is responsible for the impairment in procedural learning observed in the current study. Previous research has found that administration of a dopamine antagonist can reverse ketamine-induced impairments on the WCST, which has a procedural learning component (Krystal et al, 1999).…”
Section: Discussionmentioning
confidence: 68%
“…Likewise, PCP itself increases the firing rate of dopaminergic neurons (Freedman and Bunney 1984; French 1994). The available data suggest that acute administration of PCP may reduce cortical GABAergic function (Grunze et al 1994;Yonezawa et al 1998), disinhibiting glutamatergic transmission in the prefrontal cortex (Moghaddam et al 1997) and ventral tegmental area (Mathe et al 1998). This increase in glutamatergic transmission would then stimulate mesocorticolimbic dopaminergic transmission and locomotor behavior (Jentsch et al 1998d).…”
Section: Neurochemistry Cortical Dopamine Dysfunctionmentioning
confidence: 99%
“…Although acute PCP or ketamine administration may be associated with blockade (and net hypoactivity) of the NMDA receptor, the comprehensive effects of these drugs on cortical circuitry are complicated by the finding that acute administration of ketamine or PCP dramatically increases cortical glutamate (and dopamine) efflux (Moghaddam et al 1997), possibly leading to hyperactivation of non-NMDA glutamate receptors; this hyperactivation of glutamatergic transmission at non-NMDA receptors is a component of Olney and Farber's (1995) "NMDA receptor hypofunction" hypothesis of PCP-induced psychosis. This could also explain the seemingly paradoxical finding that acute ingestion of high doses of PCP, although reducing NMDA-associated transmission, can be proconvulsant (Gorelick and Balster 1994).…”
Section: Glutamatergic and Gabaergic Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations